Detailed transmission electron microscopy study on the mechanism of dislocation loop rafting in tungsten. (1st April 2018) - El-Atwani, O.; Aydogan, E.; Esquivel, E.; Efe, M.; Wang, Y.Q.; Maloy, S.A.
Abstract: Dislocation loop rafting and dislocation decoration have been previously observed in neutron and heavy ion irradiated materials. Understanding the fundamental aspects of these phenomena assist in evaluating irradiation damage of nuclear materials. Multiple different mechanisms have been suggested to explain loop rafting. Here, we performed a detailed transmission electron microscopy study on dislocation loop rafts in heavy ion irradiated tungsten. Different imaging conditions showed that the rafts are of <111> Burgers vector type and specifically the same <111> Burgers vector variant (<1 1 ¯ 1>) in the particular grain analyzed. Some rafts were associated with dislocation lines while some form as a result of alignment of dislocation loops. They were shown to form at both room temperature (RT) and high temperature with stronger rafts forming at RT. These observations confirm the mechanism previously suggested by Wen et al. which explains raft formation due to loop glide, cluster-cluster and grown-in dislocation-cluster interaction with subsequent Burgers vector rotation. Similar irradiation studies on nanocrystalline tungsten showed that these materials are more resistant to raft formation at RT irradiations. Graphical abstract: Image 1